Efficiency in Islamic and Conventional Banking in Indonesia - Faiza Husnayeni Nahar; Mufti Alam Adha; Rofiul Wahyudi (Department of Islamic Economics, Islamic University of Indonesia, 2022)
Islamic banking, as the relatively new player in financial services, also take parts as contributor to the growth of Indonesian economy along with the conventional one. The main purpose of this research is to analyze the efficiency of Islamic and Conventional banking in Indonesia. This research used non-parametric frontier approach, Data Envelopment Analysis (DEA), to examine the efficiency in Islamic and Conventional banks in Indonesia. It is focused on measuring technical efficiency (TE), pure technical efficiency (PTE) and scale efficiency (SE) of Islamic and Conventional banking. The finding reveals that both of Islamic and Conventional banks are relatively high on scale efficiency. On the other hand, technical is found as the least contributor to gain efficiency for banks after pure technical efficiency level. Therefore, it is suggested to bank, to manage the resources maximally, utilize information technology optimally and operate at optimum operation scale.